2007
DOI: 10.1002/chin.200746273
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics and Evolution of Alternative Splicing: The Pessimists′ Science

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 298 publications
(393 reference statements)
0
3
0
Order By: Relevance
“…We also find that G4s appear in a subset of species near splice sites ( Fig 6) which suggests that they have emerged as splicing modulators during vertebrate evolution. The presence of additional regulatory mechanisms is in accordance with higher frequencies of alternative splicing events in vertebrates compared to invertebrates (Artamonova & Gelfand 2007). Moreover, G4s display a higher likelihood of DNA mutations (Du et al 2014) and as a result they are likely plastic in nature, enabling rapid splicing changes during evolution and the establishment of new functions through alternative splicing and the generation of isoform diversity.…”
Section: Discussionmentioning
confidence: 73%
“…We also find that G4s appear in a subset of species near splice sites ( Fig 6) which suggests that they have emerged as splicing modulators during vertebrate evolution. The presence of additional regulatory mechanisms is in accordance with higher frequencies of alternative splicing events in vertebrates compared to invertebrates (Artamonova & Gelfand 2007). Moreover, G4s display a higher likelihood of DNA mutations (Du et al 2014) and as a result they are likely plastic in nature, enabling rapid splicing changes during evolution and the establishment of new functions through alternative splicing and the generation of isoform diversity.…”
Section: Discussionmentioning
confidence: 73%
“…Many studies have been published on the rate of exon insertion and deletion and on the statistics of different types of splicing, but few researchers so far have studied the evolution of transcripts [2]. Harr and Turner showed that most transcripts among Mus subspecies were novel [7].…”
Section: A Backgroundmentioning
confidence: 99%
“…Alternative splicing is a well-described biochemical process in which multiple protein isoforms are formed from a single gene, thereby increasing proteomic and functional diversity in eukaryotes (Matlin et al, 2005). Alternative splicing is tightly linked to other processes that lead to the expression of different mRNAs from one gene, such as transcription initiation using alternative promoters and alternative polyadenylation (Artamonova and Gelfand, 2007). In this study, we determined the identities of these two ZEB2 transcripts, analyzed the effects of their protein products on ZEA biosynthesis and identified their protein-interacting partners.…”
Section: Introductionmentioning
confidence: 99%